Zmiany umów w sprawie zamówień publicznych w świetle wyroku Trybunału Sprawiedliwości Unii Europejskiej z 7 grudnia 2023 r. - Wenerski, Arkady (Studia Prawa Publicznego, 2024)
The article deals with a judgment that is important from the perspective of interpreting the public procurement law on contract modifications, namely, the judgment of the CJEU of 7 December 2023. The judgment draws attention to at least two incorrect practices. First, “unforeseeable” circumstances, the occurrence of which may justify a contract modification, are sometimes interpreted too broadly. Second, contract modifications that are not made “explicitly” (by an agreement or annex modifying the contract) are not treated as contract modifications within the meaning of the regulations. The conclusions resulting from the judgment are a relevant signal for the entire public procurement market, a signal whose identification by participants in the public procurement market is mandatory. The article takes a closer look at the motives of the CJEU, as well as the implications of the ruling for participants in the public procurement market and empirical research. According to the author’s research, the contract modification rationale for the occurrence of “unforeseeable” circumstances is often used as a justification for contract modification. However, research supports the thesis that there are numerous cases in which it may be questionable to apply the rationale allowing contract modification due to the occurrence of “unforeseeable” circumstances. The correct interpretation of the CJEU judgment in question is all the more important in view of the above (the author’s research) and in terms of the potential increase in the number of public contracts (associated with the use of European Funds). Modification of a contract covered by EU funding in a manner that is not in compliance with the law may result in a 25% adjustment of the funding received.